(untitled) (Teacher’s World: Journal of Education and Research, 2024)
Scientific literacy encompasses many other big ideas, such as health literacy. In Bangladesh, there is still a dearth of studies to determine the current state of scientific literacy and health literacy. Therefore, our goal is to fill this research gap. That is to say, what is Bangladesh’s current state of scientific and health literacy? A descriptive study was carried out, the data gathered from surveys was arranged, and statistical calculations were performed. This study finds that the participants are not very interested in learning about their surroundings and are not willing to engage in scientific discussions or use scientific knowledge to influence decisions or claims made by others about common health issues. The science curriculum does, however, subtly aim to prepare the next generation of knowledgeable scientists. Therefore, one may legitimately contend that the science curriculum still lacks the clarity necessary to properly train stakeholders. The results have implications for new curricula, curriculum materials, the teaching and learning process, and the public. Teacher’s World: Journal of Education and Res arch, 50(1): 119-134